The Role Of Pedagogical, Andragogical And Heutagogical Approaches In University Students' Learning Patterns: A Cluster Analysis Study - Rofi'ah, Siti Hamidahtur; Maulidah, Evi; Abdillah, Fajar; Sauri, Achmad Sofyan; Qiptiyah, Titin Mariatul (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This study aims to analyze the learning patterns of university students in Jember Regency, Indonesia through pedagogical, andragogical, and heutagogical approaches based on five main indicators: Self-Awareness, Emotion Management, Social Awareness, Decision Making, and Student Autonomy. Data were analyzed using the K-Means Clustering method and tested for significance through ANOVA. The results of the analysis showed significant differences in the indicators of Self-Awareness (F = 34.300, Sig. = .000), Emotion Management (F = 75.472, Sig. = .000), and Decision Making (F = 11.571, Sig. = .000), while the indicators of Social Awareness (Sig. = .145) and Student Autonomy (Sig. = .952) did not show significant differences between clusters. The distance between cluster centers indicates that clusters 1 and 2 are similar, while clusters 2 and 3 show greater differences. The findings reveal that emotional management and decision-making are important factors that differentiate students’ learning patterns, while social awareness and autonomy tend to be uniform. These results are relevant to the theories of Self-Determination, Emotional Intelligence, and Constructivism which emphasize the importance of autonomy, emotional intelligence, and collaboration in learning. This study recommends the development of adaptive learning strategies that accommodate the specific needs of each cluster, with a focus on improving emotional management skills, decision-making, and independence in learning. These findings provide important contributions to the design of more inclusive and effective learning in higher education contexts.